A opacidade do financiamento da política de assistência social no ciclo orçamentário em governos locais: Algumas questões para o debate - Scatena, Rosemeire (2006)
This study has as main purpose to analyse how the budget works on financing the Social Assistance Policy in city governments, of the same region, based in the laws which determine the political content about Social Assistance from the Federal Constitution of 1988. The main argument is that the social assistant services demand has improved, the financial resources are defficient, and the city governments argue that they might not support these services by themselves. The real causes of the reducement of public financing on Social Assistance are hidden by a series of elements which has practical, conceptual, cultural and political nature. As basis, this work used the experimental examination of main instruments on public tax management planning, specifically in Social Assistance area at Campinas Metropolitan Region, from the analysis of the behaviorism and the allocated preferences on budget cycles on financing the Social Assistance at local governments. The results of this analysis pointed a lot of elements at the process of financing this policy that needed to be faced and surpassed to reach the consolidation of financing of Social Assistance at the same stage on other public social cut policies, pointing as a great challenge the joint of a new political culture which be able to embrace theoric, conceptual and technical qualification, and, also, the joint of the nature of these rights